“Perebutan Ruang Udara:” Kontestasi Jaringan Radio di Bawah Pengawasan Pemerintah Kolonial Hindia Belanda, 1934-1942 - Teofani, Debora Alfi Dwidi; Puguh, Dhanang Respati; Rochwulaningsih, Yety (Jurnal Sejarah Citra Lekha, 2025)
This article examines the contestation between the Dutch East Indies colonial government's radio networks and locally-owned private radio stations as political instruments for control and propaganda dissemination within the colony. Utilizing historical and archival research methods, this study identifies the Nederlandsch-Indische Radio Omroep Maatschappij (NIROM) as the sole government-sanctioned radio network following the enactment of the 1934 broadcasting legislation. Although under colonial ownership, NIROM incorporated Malay-language programming, initially intended as a strategic medium to neutralize nationalist movements. However, the medium underwent a functional shift as Indonesian youth co-opted radio to mobilize nationalist sentiment. This shift was propelled by the emergence of "Eastern broadcasts" (siaran ketimuran) managed entirely by indigenous youth, fostering a competitive environment between the state and local private entities. The findings demonstrate that radio served as a vital propaganda medium for independence, successfully subverting the constraints of colonial surveillance.